Electrochemical analysis of an electrodeposited Zn-Ni alloy films contained EDTA stable baths in 3.5 wt% NaCl solutions. (2020) - Anwar, Shams; Khan, Faisal; Zhang, Yahui
Abstract: The electrochemical analysis of an electrodeposited Zn-Ni alloy coating on steel substrate from a chloride bath containing ethylene-diamine-tetra-acetic acid (EDTA) was investigated in this study. Polarization tests demonstrated that the Zn-Ni alloy deposited from 0.119 M EDTA bath at 20 mA/cm 2 current density exhibited lower corrosion current (Icorr ) and more positive corrosion potential (Ecorr ). The impedance modulus and corrosion resistance were improved with a fine and robust uniform coating. At 24 h of immersion time, the samples exhibit higher corrosion resistance leads to the formation of strong corrosion product layers. The morphological properties, crystalline phases, and topographical structures of Zn-Ni coatings were characterized by scanning electron microscopy (SEM), X-ray diffraction (XRD) and atomic force microscopy (AFM). The chemical composition analysis revealed that the Zn-Ni coatings deposited from EDTA baths have higher Zn content and intensity of Ni2 Zn11 γ-phase, which exhibited better corrosion resistance properties.